Endobronchial removal of a metallic needle using a flexible diagnostic bronchoscope and biopsy forceps. A case report from Djibouti - Moaad M. Seif; Haidong Huang; Zhiang Huang; Yunye Ning; Qianbo Cheng; Chunxia Jiang; Yiyi Ma; Yide Zhou; Chong Bai; Qiang Li; Madian Mohamed Said; Konstantinos Sapalidis; et al. (Respiratory Medicine Case Reports, 2019)
Foreign body removal is a challenging procedure. Firstly we have to identify properly the foreign body and the position of the obstruction. Secondly we have to choose the proper removal equipment and finally the appropriate method of patient ventilation during the procedure. In our case report we present a challenging procedure with the removal of a metallic needle with minimum resources and equipment in a young girl in Djibouti, Africa. Keywords: Foreign body, Bronchoscopy, Biopsy forceps